Respuesta :

Space

Answer:

f(3) = -18

General Formulas and Concepts:

Pre-Algebra

  • Order of Operations: BPEMDAS

Step-by-step explanation:

Step 1: Define

f(x) = -3(x + 3)

f(3) is x = 3

Step 2: Evaluate

  1. Substitute:                    f(3) = -3(3 + 3)
  2. Add:                              f(3) = -3(6)
  3. Multiply:                        f(3) = -18

And we have our final answer!

Answer:

-18

Step-by-step explanation:

Okay.So first you got to put the value of x,which is 3 into the equation -3(x + 3).Then you got to  simpliy that like this:

-3(3 + 3)

-3(6)

-18

Hoped this helped!